PENGENALAN KONSEP BILANGAN PADA ANAK USIA DINI USIA 5-6 TAHUN MELALUI PEMBELAJARAN ONLINE PADA MASA PANDEMI COVID-19 - Titi Supriati; Asih Nur Ismiatun (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2021)
The teacher has to give education to the children even though online, because of the virus corona covid 19. The way to introduce subjects such as the concept of numbers to early childhood is through online learning. This research aims to describe and to analyzing about the concept of numbers introduction for early childhood 5-6 years old. The research uses the descriptive qualitative method. The subject research is a kindergarten teacher from AQ Assalamah school. The data collection technique used interviews, observation, and documentation. The data analysis technique used data reduction, data display, and conclusion. The results analysis describes the implementation, children, and parents' response, and the obstacles during the introduction of concept number for early childhood tare place in pandemic covid 19 periods. According to the analysis result, the implementation of concept numbers are planning, implementation and assessment. The children showed good responses and were so enthusiastic about this learning and the obstacles that were found are not all parents have handphones can to support this learning and can,t afford the quota of the internet because of the economic factor.Pembelajaran online selama masa wabah virus corona ini menuntut guru harus tetap memberikan pembelajaran pada anak PAUD  tanpa tatap muka, pembelajaran konsep berhitung termasuk di dalamnya.  Tujuan stusy ini yaitu untuk mendeskripsikan dan menganalisis pemahaman konsep berhitung melalui pembelajaran online di masa wabah virus corona. Metode deskriftif kualitatif digunakan dalam studi ini.  Subjek penelitian adalah guru Kober AQ Assalamah. Pengolahan data menggunakan wawancara, observasi, dan dekumentasi.  Analisis data menggunakan reduksi data, display data, dan kesimpulan. Hasil penelitian mendeskrifsikan implementasi, respon anak dan kendala kendalanya melalui pembelajaran online pada masa wabah virus corona. Hasil study bahwa.implementasi pembelajaran konsep bilangan terdiri dari perencanaan, pelaksanaan,  dan penilaiaan, anak menunjukan respon yang baik dan antusias mengikuti pembelajaran dan kendala yang ditemukan adalah wali murid tidak mempunyai handphone yang bisa mendukung pembelajaran dan mampu membeli kuota karena paktor ekonomi.